Heating of flint debitage from Upper Palaeolithic contexts at Manot Cave, Israel: changes in atomic organization due to heating using infrared spectroscopy. (February 2015) - Weiner, Steve; Brumfeld, Vlad; Marder, Ofer; Barzilai, Omry
Abstract: The heat treatment of flint is known to change its mechanical properties and improve its fracture behaviour during knapping. Here we examine 20 flint artifacts from Upper Paleolithic contexts from Manot Cave, Israel, using Fourier transform infrared spectroscopy and compare them to geogenic flint beds from the walls inside the cave and from outcrops just above the cave. We show that the 512 and 467 cm −1 peaks are broader in most of the flint debitage pieces as compared to the geogenic flint, and that broadening of these peaks occurs when geogenic flint from the cave wall is heated. We also present an empirical simple method to monitor these changes. Highlights: New FTIR method for determining whether flint was heated in antiquity. Almost all debitage fragments from Manot Cave, Israel, were heated in antiquity. Both peak deconvolution and peak height measurements provide the same results.